2018
DOI: 10.1080/10803548.2018.1501972
|View full text |Cite
|
Sign up to set email alerts
|

Impact of posture and upper-limb muscle activity on grip strength

Abstract: Higher values of GS were attained in standing postures which may result in attainment of higher performance levels by the workers. The outcomes justify the importance of correct postures during manual work in industries employing traditional methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…In the present study, we regarded the variation of hand grip strength for holding a cleaner handle as a phenomenon that could naturally happen during vacuuming with a stick-type vacuum cleaner, and thus the grip strength was not considered a parameter that had to be observed separately with interest during testing. However, it has been demonstrated that grip strength for holding a handle is associated with the muscle activities (especially, the ECU and BR) of the upper limbs [58,59]. Thus, further studies to find out the extent to which the grip strength contributes to the muscle activities of the upper limb could be useful for advancing the validity of the present study.…”
Section: Implications and Limitationsmentioning
confidence: 77%
“…In the present study, we regarded the variation of hand grip strength for holding a cleaner handle as a phenomenon that could naturally happen during vacuuming with a stick-type vacuum cleaner, and thus the grip strength was not considered a parameter that had to be observed separately with interest during testing. However, it has been demonstrated that grip strength for holding a handle is associated with the muscle activities (especially, the ECU and BR) of the upper limbs [58,59]. Thus, further studies to find out the extent to which the grip strength contributes to the muscle activities of the upper limb could be useful for advancing the validity of the present study.…”
Section: Implications and Limitationsmentioning
confidence: 77%
“…The daily manual operation should be performed in the posture with optimum grip strength which is suggested for good occupational health and their safety at workplace. The suitable grip strength data is recommended for tool/equipment design for manual working in unorganized sectors 6) .…”
Section: Introductionmentioning
confidence: 99%
“…Repetitive tasks in awkward postures are a major risk factor. The posture of the upper limbs and the applied force are related [ 3 , 4 ]. Maximum force can be developed with the shoulder forward at 45°, elbow at 90°, and a neutral position of the wrist and forearm [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The posture of the upper limbs and the applied force are related [ 3 , 4 ]. Maximum force can be developed with the shoulder forward at 45°, elbow at 90°, and a neutral position of the wrist and forearm [ 3 ]. This posture also allows for better efficiency of force production.…”
Section: Introductionmentioning
confidence: 99%